Bacterial growth and recovery on hospital biometric devices: effect of two types of disinfectants - Norton, P (2021)
Objectives: The aim of the study was to evaluate the presence of bacterial contamination on biometric identification devices in a public hospital; identify the species of bacteria implicated in the contamination and assess bacterial recovery after the use of 2 types of disinfectants: alcohol 70% and isopropyl alcohol chlorhexidine. Design: Before and after trial. Setting: Public hospital, tertiary referral center. Participants: All existing biometric identification devices in the hospital (n = 20). Methods: Collection of 2 microbiological samples from the fingerprint reading surface of biometric devices immediately before and after applying the solution with alcohol 70% and in separate time periods with isopropyl alcohol chlorhexidine. Results: It have been identified 21 different bacterial species in a total of 78 samples, mostly Staphylococcus epidermidis (32 samples) and S aureus (7 samples). S epidermidis was eliminated in 61.5% of the samples after disinfecting with alcohol 70% and in 92.3% of the samples disinfected with isopropyl alcohol chlorhexidine. S aureus was eliminated in 33.3% and 100% of the samples, respectively. We found no bacterial growth in 10% of the devices after disinfection with 70% alcohol and in 78.9% of devices after disinfection with isopropyl alcohol chlorhexidine. We also found that there was a decrease in the frequency of species isolated after using both disinfection solutions, although isopropyl alcohol chlorhexidine appeared to be more effective. Conclusions: The biometric identification devices used in this hospital seem to be safe regardless of the products used for its cleaning. The majority of the bacteria found are commensal skin microorganisms. We did not find pathogenic bacteria for immunocompetent individuals, in particular methicillin-resistant S aureus.